A qualitative examination of barriers and solutions to renal transplantation in Malaysia: Key-informants’ perspective - Gan, Peter Kim Soon; Lim, Soo Kun; Rampal, Sanjay; Tin, Tin Su (Public Library of Science, 2019)
Introduction End-stage renal disease (ESRD) is increasing globally, and renal transplantation (RT) is the preferred renal replacement therapy to treat ESRD. Internationally, there are only a few countries with RT rates above 50 per million population (pmp), while most of the countries have RT rates between 30-40 pmp. The low- and middle-income countries (LMIC) makes up the majority for the RT rates below 20 pmp in which Malaysia belongs to despite its increasing ESRD rates. There is a need to explore the barriers to access RT with targeted solutions to improve the RT rates and service in LMIC. Thus, a qualitative study was undertaken in Malaysia to address this issue. Method A qualitative methodological approach was performed between March-May 2018. Semistructured interviews were used to explore current RT policy and service availability. Keyinformants were identified from a detailed stakeholder analysis of RT system in Malaysia. Interviews were digitally audio-recorded, transcribed verbatim, coded with ATLAS.ti software and underwent thematic analysis thoroughly. Results Eight key-informants participated in the study. Barriers and related solutions were classified using the socio-ecological model (SEM). As reported, the barriers and solutions of RT in Malaysia are the results of a complex interplay of personal, cultural, and environmental factors. Key barriers are linked to public's attitude and perception towards RT and the unaccommodating practices in the healthcare fraternity for RT. Key-informants provided a systematic solution that shed light on how RT could be improved at each SEM level via effective communication, education and inter-agency collaboration. Conclusion The SEM provided a framework to foster a better understanding of current practice, barriers, and solutions to RT in Malaysia. This study is the first to explore the barriers and related solutions to RT comprehensively as a whole. Implications of these findings could prompt a policy change for a better RT service delivery model not just for Malaysia but also for other LMIC. Further stakeholder engagement and evaluation of the systems are required to provide insight into best practices that will help to improve the RT rates and service in Malaysia. © 2019 Gan Kim Soon et al.